Respuesta :

Answer:

I got you

Step-by-step explanation:

f= 19

Simplifying
8 = F + -1(13 + -2)

Combine like terms: 13 + -2 = 11
8 = F + -1(11)

Multiply -1 * 11
8 = F + -11

Reorder the terms:
8 = -11 + F

Solving
8 = -11 + F

Solving for variable 'F'.

Move all terms containing F to the left, all other terms to the right.

Add '-1F' to each side of the equation.
8 + -1F = -11 + F + -1F

Combine like terms: F + -1F = 0
8 + -1F = -11 + 0
8 + -1F = -11

Add '-8' to each side of the equation.
8 + -8 + -1F = -11 + -8

Combine like terms: 8 + -8 = 0
0 + -1F = -11 + -8
-1F = -11 + -8

Combine like terms: -11 + -8 = -19
-1F = -19

Divide each side by '-1'.
F = 19

Simplifying
F = 19
ACCESS MORE